BUREAUCRACY IN THE UNITED STATES OF AMERICA: A Review of Corporate Policies in the Period of Governance Donald Trump - Azmy, Ana (CosmoGov: Jurnal Ilmu Pemerintahan, 2020)
One of the policies for corporations that reap the pros and cons of Donald Trumps administration is the Tax Reform Act, known as the Tax Cuts and Jobs Act (TCJA)2018. Important points of the Act are: 1) changing the Corporate Income Tax rates from 35% to 21% and a drastic reduction that gives tax discounts of up to 60%. 2) change from worldwide to a territorial system. The tax reform was carried out because Trump saw the US tax system was no longer competitive. After all, it had a high corporate income tax rate of 35% and adopted a worldwide tax system. Pros and cons in discussing this law are that the outcome of the political process contained in the Act is not the same as the initial points put forward by Trump. Using literature studies from various libraries, this paper reviews the characteristics of the bureaucracy in the United States, by looking at the phenomenon of policies issued to corporations during Donald Trumps administration. This paper concludes that the characteristics of bureaucracy in the US tend to dominate institutions; the level of importance is different for each stage. Bureaucracy is seen as an instrument of power for the elite in running the government.gb777